Pengaruh Komunikasi Word Of Mouth Terhadap Keputusan Pembelian Di Restoran Simpang Raya Pasteur Bandung The Influence of Word of Mouth to Buying in Simpang Raya Restaurant Pasteur Bandung - Rosalina, Juniartha; Tiorida, Ermida (Jurnal Riset Bisnis dan Investasi, 2016)
This study aims to determine word of mouth communication and purchasing decisions in Simpang Raya Restaurant Pasteur, and knowing how word of mouth communication influence on purchasing decisions in Simpang Raya Restaurant Pasteur. This study was a survey research type of research that the information collected from respondents using a questionnaire. The study population was all purchasers in Resoran Simpang Raya Pasteur. The sampling method used in this research is non-probability sampling with accidental sampling technique with 100 respondents. Data collection techniques using questionnaires that have been tested for validity and reliability. Data analysis technique used is descriptive analysis, correlation analysis, and simple linear regression analysis. The results showed that word of mouth communication positively related to purchasing decisions in Simpang Raya Restaurant Pasteur. Communication word of mouth in Simpang Raya Restaurant Pasteur is in the category fairly with the average response of 3.24 and purchasing decisions in Simpang Raya Restaurant Pasteur is the category of good/high with the mean average response of 3.57. Communication word of mouth give influence to purchasing decisions amounted 35.4%. The rest was influenced by other variables not examined in this study in the amount of 64.6%. The other variable is the cultural factors, personal factors, and psychological factors. Suggestions for the company based on the conclusion, Simpang Raya Restaurant Pasteur is expected to improve the quality of service that consumers were satisfied and had no complaints about Simpang Raya Restaurant Pasteur. So word of mouth communication is positive by consumer and ends on the repurchase and the emergence of potential buyers. Then, Simpang Raya Pasteur is expected to enable the public relations to complete the deployment of negative WOM communication via electronic media, namely the Internet.